Assessment of oil slick hazard and risk at vulnerable coastal sites. Issue 1 (15th May 2015) - Melaku Canu, Donata; Solidoro, Cosimo; Bandelj, Vinko; Quattrocchi, Giovanni; Sorgente, Roberto; Olita, Antonio; Fazioli, Leopoldo; Cucco, Andrea
Highlights: We assessed the hazard faced by Sicily coasts related to potential oil spill events. We simulated 4380 spills using a suite of high resolution models. Hazard indexes were computed from statistic analysis of model results. Vulnerability of marine protected area has been considered. A risk index was computed by combining hazard and vulnerabilities. Abstract: This work gives an assessment of the hazard faced by Sicily coasts regarding potential offshore surface oil spill events and provides a risk assessment for Sites of Community Importance (SCI) and Special Protection Areas (SPA). A lagrangian module, coupled with a high resolution finite element three dimensional hydrodynamic model, was used to track the ensemble of a large number of surface trajectories followed by particles released over 6 selected areas located inside the Sicily Channel. The analysis was carried out under multiple scenarios of meteorological conditions. Oil evaporation, oil weathering, and shore stranding are also considered. Seasonal hazard maps for different stranding times and seasonal risk maps were then produced for the whole Sicilian coastline. The results highlight that depending on the meteo-marine conditions, particles can reach different areas of the Sicily coast, including its northern side, and illustrate how impacts can be greatly reduced through prompt implementation of mitigation strategies.